Can Walking Motions Improve Visually Induced Rotational Self-Motion Illusions in Virtual Reality? - Riecke, Bernhard E.; Freiberg, Jacob; Grechkin, Timofey Y. (Journal of Vision, 2015)
Illusions of self-motion (vection) can provide compelling sensations of moving through virtual environ- ments without the need for complex motion simulators or large tracked physical walking spaces. Here we explore the interaction between biomechanical cues (stepping along a rotating circular treadmill) and visual cues (viewing simulated self-rotation) for providing stationary users a compelling sensation of ro- tational self-motion (circular vection). When tested individually, biomechanical and visual cues were similarly effective in eliciting self-motion illusions. However, in combination they yielded significantly more intense and convincing self-motion illusions, and lead to earlier onset of the rotational self-motion illusion. These findings provide the first compelling evidence that walking motions can be used to sig- nificantly enhance rotational self-motion perception in virtual environments without having to provide for physical self-motion or motion platforms. This is noteworthy, as linear treadmills have been found to actually impair visually-induced translational self-motion perception (Ash et al., 2013). Given the predominant focus on linear walking interfaces for VR locomotion, our findings suggest that investigating circular walking interfaces offers a promising direction for future research and development.
Keywords: DG2019; Riecke; Riecke_2015; bernhard-riecke; biomechanical vection; circular treadmill; circular vection; jake-freiberg; journalPaper; multi-modal vection; timofey-grechkin; vection